Charity within the Estates in the Russian Empire in the 19th Century - Pokotilova, Tatyana Evgenevna; Sinkov, Dmitry Vladimirovich; Okorokova, Olga Alekseevna (Journal of History Culture and Art Research, 2019)
The article deals with the issues of implementing the principle of estates in the system of social care in the 19th century in Russia, a country with the centuries-old tradition of charity and the population’s structure that was represented with social estates as the main social groups vested with statutory duties and rights. The analysis focuses on the main forms and features of intra-estate charity among Russian peasants and merchants. The peasantry was the largest Russian estate, which, due to its social and financial position, had a constant need for large-scale social assistance in its various forms. The merchant class was the most secure, having a rich history of charitable activity in relation to representatives of all economically insolvent social groups, and, like all other Russian social estates, was vested with the primary statutory duty to take care of the "insufficient" members of their class.